The shelters of stone [compact disc, unabridged] - Auel, Jean M. (Auel, Jean M. Earth's children., 2011)
Ayla and Jondalar continue their epic journey across Ice Age Europe to join Jondalar's people, the Zelandonii, confronting new hardships and perilous challenges along the way.